Potensi Chilling Effect Tindak Pidana Penghinaan terhadap Kebebasan Berpendapat - Ayumi, Rara Bunga; Rusdiana, Emmilia (Diktum: Jurnal Ilmu Hukum, 2026)
Freedom of expression is a fundamental right in democratic states, functioning as a means of public participation and oversight of power. However, this right may be restricted through criminal law to protect individual honor and maintain public order. Problems arise when criminal defamation norms are broadly formulated and lack clear limitations, creating legal uncertainty in their enforcement. Such conditions may generate a chilling effect, where individuals restrain expression due to fear of criminal sanctions. This study aims to analyze the concept of the chilling effect in restricting freedom of expression and evaluate criminal defamation regulations from a legal certainty perspective. Using normative legal research methods, this study finds that broadly interpreted norms may encourage self-censorship, highlighting the need for clearer, more precise, and proportionate legal formulations. The findings also imply that ambiguous insult provisions in the Indonesian Penal Code risk undermining democratic discourse and require judicial safeguards to prevent excessive restriction of public criticism. Therefore, a balanced approach between reputation protection and freedom of expression is essential.